ACUTE DERMAL TOXICITY STUDY OF ARECA CATECHU LINN. EXTRACT IN SPRAGUE-DAWLEY RATS - Sari, Liza Meutia; Suyatna, Frans D; Subita, Gus Permana; Auerkar, Elza Ibrahim (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Areca catechu Linn. or biji pinang is one of the most widely used psychoactive substance with several hundred million users worldwide, predominantly in Southern Asia. However, details of the dermal toxicity of A. catechu L. are still undiscovered. The objective of this study is to investigate the in vivo acute dermal toxicity of aqueous extract of A. catechu L. at dose 15,000 mg/kg body weight in Sprague-Dawley rats. Methods: The acute dermal toxicity of A. catechu L. nut extract was investigated in rats, as per OECD Guidelines 402 for acute toxicity protocols. The body weight, possibility of death, general signs, and behavior activity parameters were measured for 14 days to ascertain the median lethal dose (LD50) of the extract. At the end of the study, all the animals in all the treated group were sacrificed. Results: The LD50 was found to be >15,000 mg/kg body weight. There was significant weight increase (p<0.05) in treated group when compared to control group. No mortality was observed during whole 14 days study period. A single dose of 15,000 mg/kg of body weight did not produce treatment-related signs of toxicity in any of animal tested. Conclusion: A single dermal dose to A. catechu L. aqueous extract had no toxic effects on mortality, clinical signs, body weight changes, and gross findings in female rats at a dose of 15,000 mg/kg of body weight. Subsequently, the concentrate can be employed for pharmaceuticals nutrient plants. Keywords: A. catechu L., Acute dermal toxicity, LD50.